Designing a STEM-Based Learning Trajectory for Understanding Median Through Coffee pH Measurement Activities - Susanti, Novi; Putri, Ratu Ilma Indra; Aisyah, Nyimas; Hartono, Hartono (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
This study addressed students’ difficulties in understanding the median as a conceptual measure of central tendency rather than a procedural computation. It aimed to design and validate a STEM-based learning trajectory to support students’ understanding of the median through coffee pH measurement activities. The study employed a design research methodology of the validation study type, consisting of a preliminary design, pilot experiment, teaching experiment, and retrospective analysis. The subjects were tenth-grade vocational high school students in Palembang majoring in culinary arts. Data were collected through classroom observations, student worksheets, semi-structured interviews, and video recordings. The results showed that the STEM-based learning trajectory enabled students to progress from concrete data collection to data organization, identification of the middle position, formal median calculation, and contextual interpretation. The instructional design can support students’ conceptual understanding. A STEM-based learning trajectory using the context of coffee pH measurement can serve as an alternative instructional strategy to help students gradually develop a conceptual understanding of the median while simultaneously enhancing statistical literacy through authentic experiences of collecting, processing, and interpreting data.